Konstruksi Identitas Keagamaan LDII dalam Wacana Moderasi Beragama: Sebuah Tinjauan Sistematis - Faqih Abdul Aziz; Rohmat Robi' Rozaqiy; Adept Wahyu Wijaya; Iffatut Tazkiyyah; Abdullah Hasan Busri (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
The construction of religious identity among minority Islamic organizations within Indonesia’s religious moderation landscape represents a complex and continuously negotiated terrain. This article presents a Systematic Literature Review (SLR) of 30 national and international journal articles to map how academic literature constructs the religious identity of Lembaga Dakwah Islam Indonesia (LDII) amid the tension between inherited historical stigma and demands to adapt to religious moderation discourse. Drawing on Berger-Luckmann’s Social Construction theory and Goffman’s Stigma theory, qualitative thematic synthesis produced three main themes: construction of stigma and exclusivism labeling; dynamics of adaptation and identity renegotiation; and LDII’s positioning within the hegemony of national religious moderation discourse. Findings reveal that LDII’s religious identity is fluid, negotiated, and contextual not a static entity imprisoned by historical stigma. LDII actively responds to stigmatization through institutional transformation, social philanthropy, and theological reorientation toward moderation. This study contributes to the sociology of religion in Indonesia by offering a discursive map that transcends the stigma-adaptation dichotomy, and implies the urgency of more inclusive religious moderation policies for all Islamic movement entities in Indonesia.